MIKROPROPAGASI IN VITRO JERUK KUOK (Citrus Nobilis Lour) MENGGUNAKAN HORMON 2,4-D DAN TDZ (THIDIAZHURON) SEBAGAI RANCANGAN MODUL PEMBELAJARAN BIOLOGI DI SMA - Firman Syah; Imam Mahadi; Darmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Sweet fruits Kuok is a name which is pinned by community of citrus 9lemon) that was developed in Kampar ,Riau . A study to determine the effect of 2,4-D and TDZ(thidiazhuron) on the growth of fruit Kuok explanations (citur nobilis Lour) as learning module was designed by high school which is conducted in May and June 2016 in labolatory of agriculture UIR. This study used an experimental method with a completely andom design (CRD) with two factors, the first factor (D) is 2,4-D and the second (T) is TDZ consisting of 25 treatments, each treatment was repeated three time until three are 75 experimental units . These results indicate the effect of 2,4-D and TDZ significantlyaffect the growth of jeruk Kuok explanation.The percentage of time that the fastest growing explanations D4T2 100%,D4T2 treatment plant height 3.0 cm, number of leaves D4T2 5.3 bh treatment,the number of root treatment D4T2 7.0 bh. From the data generated will be developed as a learning module design in high school biology in Biotechnology modren material.Key Words: Mikropropagasi, Fruits Kuok, 2,4-D,TDZ, Modern Material